Hubungan Volume, Kecepatan dan Kepadatan Lalu Lintas pada Jalan Kabupaten Aceh Tamiang - Chairumansyah, T; Masthura, Lely; Basrin, Defry (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2024)
Highways are a very important transportation infrastructure in helping regional development, so that without a smooth flow of transportation it will have a lot of influence in encouraging the rate of development which tends to increase community growth. Therefore, a comprehensive road monitoring system is needed in order to find out the problems of congestion on the road. The method used in this research is the greenshields and underwood method. The aim of the research is to obtain the volume, speed and density of traffic and obtain a graph of the relationship between volume, speed and traffic density on the Banda Aceh – Medan STA road. 464+700 to STA. 465+200 Kedai Besi Village, Karang Baru District, Aceh Tamiang Regency. The research results were obtained for the direction Langsa - Kuala Simpang S-D (Speed-Density), with the highest R² value (R² = 0.198). V-D (Volume-Density), with the highest R² value (R² = 0.988). V-D (Volume-Speed) with the highest R² value (R² = 0.537). Meanwhile, for the direction Kuala Simpang – Langsa S-D (Speed-Density), with the highest R² value (R² = 0, 0.999). V-D (Volume-Density), with the highest R² value (R² = 0.991). V-D (Volume-Speed) with the highest R² value (R² = 0.209). From the research results for the Kuala Simpang - Langsa road, it is more suitable to use the underwood model. Meanwhile, for the Langsa - Kuala Simpang direction, it is more suitable to use the greenshields model. Keywords: Greenshields, Highways, Transportation, Underwood.